PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAH, SISTEM AKUNTANSI KEUANGAN DAERAH DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KUALITAS LAPORAN KEUANGAN PADA RUMAH SAKIT UMUM DAERAH KABUPATEN BANGLI - Vidyantari, Putu Kemala; Putra, I Wayan Gde Yogiswara Darma; Putri, Putu Yudha Asteria; Diana, Ketut (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This study aims to examine the influence of the implementation of government accounting standards, regional financial accounting systems, and human resource competencies on the quality of financial reports at the Bangli District General Hospital. The study population consists of 181 employees from various departments, with a sample size of 45 people selected using Slovin's formula at a 25% margin of error. The research method used is quantitative, with primary data as the data source. Data analysis employs multiple linear regression analysis using SPSS. The results of this study provide empirical evidence that, partially, the variables of the implementation of government accounting standards, regional financial accounting systems, and human resource competencies have a positive effect on the quality of financial reports at the Bangli District General Hospital. Simultaneously, these variables significantly influence the quality of financial reports at the Bangli District General Hospital